Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan - Yulandri Yulandri; Onsardi Onsardi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to study compensation and work discipline on employee performance at PT (SBS) Sinar Bengkulu Selatan. The research method in this study uses quantitative research methods. The results of the study can be concluded regarding the respondents' perceptions about Compensation Location (X1) and Work Discipline (X2) Employee Performance results (Y) with the results of multiple linear regression obtained the following research results: Y = 14.876 + 0.277X1 + 0.795X2 analysis of responses R = 0.823 ( X1) -Y), 0.926 (X2-Y) and the coefficient of determination R2 = 0.521 or approximately (52.51%) through testing the hypotheses together (simultaneously) and individuals (partial) in this study using the f test and t test, compensation (X1) and work discipline (X2), = 0,000. Conclusion, significant significant contribution and work discipline to employees at PT (SBS) Sinar Bengkulu Selatan. Keywords: Work Discipline, Employee Performance, Compensation